Synthesis of peptidoglycan and teichoic acid in Bacillus subtilis: role of the electrochemical proton gradient. - Harrington, C R (1984)
The effects of several ionophores and uncouplers on glycerol and N-acetylglucosamine incorporation by Bacillus subtilis 61360, a glycerol auxotroph, were tested at different pH values. In particular, the effect of valinomycin on the synthesis of teichoic acid and peptidoglycan was examined in more detail in both growing cells and in vitro biosynthetic systems. Valinomycin inhibited synthesis of wall teichoic acid and peptidoglycan in whole cells but not in the comparable in vitro systems. It did not inhibit formation of free lipid or lipoteichoic acid. The results were consistent with a role for the electrochemical proton gradient in maintaining full activity of cell wall synthetic enzymes in intact cells. Such an energy source would be required for a model in which rotation or reorientation of synthetic enzyme complexes is envisaged for the translocation of wall precursor molecules across the cytoplasmic membrane (Harrington and Baddiley, J. Bacteriol. 155:776-792, 1983).